Agentic AI for Personalized Education and Adaptive Learning Environments - Babar, Pramod Appa (International Journal of Computing and Engineering, 2025)
This article explores agentic artificial intelligence in educational environments, focusing on its transformative potential for personalized learning experiences. Agentic AI, characterized by autonomous goal-driven systems, leverages advanced technologies like large language models and reinforcement learning to dynamically adapt to individual learner needs. The discussion encompasses the technological foundations underlying these systems, architectural approaches that enable their functionality, case studies demonstrating successful implementations across various educational contexts, and critical ethical considerations alongside implementation challenges. By examining how these intelligent systems continuously assess and respond to learner performance, preferences, and engagement in real-time, the article illuminates how agentic AI can democratize access to quality education, address diverse learning needs, and empower educators through complementary technological assistance rather than replacement. Integrating these sophisticated technologies marks a paradigm shift from traditional standardized approaches toward responsive, learner-centered educational ecosystems that recognize and accommodate individual differences while simultaneously addressing systemic challenges such as teacher shortages, resource limitations, and the growing demand for lifelong learning opportunities in an increasingly complex knowledge economy.